Bioactive xanthoquinodins and epipolythiodioxopiperazines from Chaetomium globosum 7s-1, an endophytic fungus isolated from Rhapis cochinchinensis (Lour.) Mart - Tantapakul, Cholpisut; Promgool, Trinop; Kanokmedhakul, Kwanjai; Soytong, Kasem; Song, Jiaojiao; Hadsadee, Sarinya; Jungsuttiwong, Siriporn; Kanokmedhakul, Somdej (My University, 2020)
A new xanthoquinodin B9 (1), together with two known xanthoquinodins, xanthoquinodin A1 (2) and xanthoquinodin A3 (3), three epipolythiodioxopiperazines, chetomin (4), chaetocochin C (5) and dethio-tetra(methylthio)chetomin (6), and four other compounds, chrysophanol (7), emodin (8), alatinone (9), and ergosterol (10) were isolated from the endophytic fungus Chaetomium globosum 7s-1, isolated from Rhapis cochinchinensis (Lour.) Mart. All isolated structures were established based on their spectroscopic data analyses. Compounds 1–6 showed antibacterial activity against Gram positive bacteria with MICs ranging from 0.02 pM to 10.81 µM. Compounds 1–6 also exhibited cytotoxicity against KB, MCF-7 and NCI-H187 cancer cell lines (IC50 0.04–18.40 µM). However, they were cytotoxic towards a normal cell line (Vero cell) with IC50 values ranging from 0.04 to 3.86 µM.
Keywords: antibacterial; Chaetomium globosum; cytotoxicity; epipolythiodioxopiperazine; xanthoquinodin